A prospective study on body image disturbances during pregnancy and postpartum: the role of cognitive reappraisal - Spinoni, Marta; Singh Solorzano, Claudio; Grano, Caterina (Frontiers in Psychology, 2023)
Background: During pregnancy, body size rapidly modifies over a relatively short period. Literature emphasizes the need to identify the factors that influence body image during peripartum as the extent of women's adaptation to these changes has significant repercussions on both mother's and newborn's health. Emotion regulation strategies (i.e., expressive suppression and cognitive reappraisal) were linked to body image in the general and clinical population, but no studies were conducted in the peripartum. The present study aims to investigate the longitudinal impact of prepartum body image disturbances on postpartum body image disturbances and to evaluate the mediational role of emotional regulation strategies. Methods: A total of 133 pregnant women completed a three-phase longitudinal study. Women answered online questionnaires during the second (T1) and the third (T2) trimesters of pregnancy, and at about six months postpartum (T3). Results: Findings indicated that body image disturbances at T1 were a significant predictor of body image disturbances in the postpartum (1 year after the first assessment). Moreover, cognitive reappraisal measured at T2 partially mediated this relationship: body image disturbances in the second trimester of pregnancy were linked to less use of cognitive reappraisal in the third trimester of pregnancy, and this, in turn, was associated with worse body image disturbances at six months after birth.Findings of this longitudinal study highlight the importance of assessing body image disturbances during pregnancy to early identify women at risk, and suggest cognitive reappraisal as a possible target intervention.